2017
DOI: 10.1097/moh.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of late events in erythropoiesis by KLF1/EKLF

Abstract: Purpose of review Transcriptional regulators provide the molecular and biochemical basis for the cell specific properties and characteristics that follow from their central role in establishing tissue restricted expression. Precise and sequential control of terminal cell divisions, nuclear condensation, and enucleation are defining characteristics within erythropoietic differentiation. This review is focused on KLF1, a central global regulator of this process. Recent findings Studies in the past year have br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 80 publications
(77 reference statements)
0
37
0
Order By: Relevance
“…E2F‐2 controls erythroblast enucleation by inducing expression of citron Rho‐interacting kinase, a mitotic kinase that regulates astral microtubule length and spindle orientation in dividing cells, participates in nuclear condensation, and is involved in contractile actin ring formation 25 . Before enucleation, erythroblasts exit the mitotic cell cycle which requires sequential control of genes which both accentuate S phase progression (eg, E2F‐2) and enable exit from the cell cycle (eg, p27) 45 . Our results suggested that rapamycin treatment might increase E2F‐2 and p27 production and promote cells exit from the cell cycle, thereby accelerating enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…E2F‐2 controls erythroblast enucleation by inducing expression of citron Rho‐interacting kinase, a mitotic kinase that regulates astral microtubule length and spindle orientation in dividing cells, participates in nuclear condensation, and is involved in contractile actin ring formation 25 . Before enucleation, erythroblasts exit the mitotic cell cycle which requires sequential control of genes which both accentuate S phase progression (eg, E2F‐2) and enable exit from the cell cycle (eg, p27) 45 . Our results suggested that rapamycin treatment might increase E2F‐2 and p27 production and promote cells exit from the cell cycle, thereby accelerating enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal erythropoiesis is a series of dynamic and intricate processes involving fine coordination of gene expression, cell proliferation, hemoglobin production, cell size decrease, cell cycle exit, chromatin condensation, and enucleation. [10][11][12] Using RNA-sequencing data from human and mouse terminal erythropoiesis, 13,14 we found that 16 conserved highly expressed genes were at least twofold upregulated both from the murine R2 to R4 or R5 stages and from human proerythroblasts to orthochromatic or polychromatic erythroblasts. Among these genes, PHOSPHO1 is the only one directly related to PC metabolism.…”
Section: Increased Phosphocholine Metabolism During Terminal Erythropmentioning
confidence: 95%
“…In addition, nucleus expulsion is believed to be dependent on adhesion protein reorganization across the PM and macrophage interactions (Lee et al, 2004 ; Soni et al, 2006 ). The transcription factor KFL1 is required for enucleation (Parkins et al, 1995 ; Magor et al, 2015 ), regulating the expression of cell cycle proteins, deacetylases, caspases, and nuclear membrane proteins (Gnanapragasam et al, 2016 ; Gnanapragasam and Bieker, 2017 ).…”
Section: Enucleationmentioning
confidence: 99%
“…With the same model, the role of HDAC2 protein was shown to be essential not only for chromatin condensation but also for the formation of the contractile actin ring (CAR), which is involved in nuclear pyknosis (Ji et al, 2010 ). Moreover, it was recently shown that major histones are released through a nuclear opening that is induced by caspase 3 activity-dependent lamin B cleavage and chromatin condensation (Gnanapragasam and Bieker, 2017 ).…”
Section: Enucleationmentioning
confidence: 99%